Självkostnadsprincipen i AB 04 – särskilt om entreprenörens skyldighet att åstadkomma bästa tekniska och ekonomiska resultat - Wihlstrand,Oskar (2024)
Pursuant to AB 04 chapter 6 section 10 item 1, the contractor is obligated to perform their work in such a manner that the client receives both the best technical and economic result. In practice, these two outcomes are often difficult to achieve, since they rarely correlate. Additional complexity arises from the contractor’s incentive to maximise profit. Because the contractor’s fee is often calculated as a percentage markup on costs, an inherent conflict arises. Technical quality tends to increase costs and thereby the contractor’s profit, while cost minimization may occur at the expense of technical standards, which in turn could negatively impact the contractor’s profit. This conflict between technical quality, economic optimisation and profit creates a delicate balance, making the regulation in AB 04 chapter 6 section 10 item 1 challenging to apply in practice. The consequence is limited predictability for both the client and the contractor, as it is rarely clear how these conflicting interests should be balanced in individual cases. This thesis analyses this issue and emphasises that the contractor’s obligation should be understood as a duty of care rather than as an obligation of result. This means that the contractor must act professionally and cost-consciously, striving for the best technical and economic outcome, but without being required to guarantee an objectively optimal result. Furthermore, it is noted that the burden of proof to demonstrate deviations from the duty of care lies with the client, while the contractor, on their part, must be able to account for their costs transparently and adequately to justify their entitlement to compensation. Despite this clear allocation of responsibility, it becomes evident that, in practice, the client often bears a disproportionately large share of the economic risk. The active role expected of the client in reviewing and questioning the contractor’s costs is both resourceintensive and complex. This further inhibits the ability to achieve a predictable and fair distribution of risk between the parties. The concept of professionalism (Sw: fackmässighet), which seems to play a central role in defining the contractor’s obligations in performing the contract, is characterised by ambiguity and a lack of uniform guidelines for interpretation and application. In the draft of AB 25, the requirement of professionalism has been integrated into the provision corresponding to AB 04 chapter 6 section 10 item 1. Despite this clearer connection, significant uncertainties remain, which risk maintaining legal uncertainty and complicating predictable application in practice. The thesis highlights that AB 04 chapter 6 section 10 item 1 is characterised by inherent conflicts and ambiguities, making its practical application challenging. The uneven distribution of risk, where the client often bears a disproportionately large share of the economic risk, combined with the lack of uniform guidelines for interpreting and applying both the requirement of professionalism and the contractor’s duty of care, creates significant challenges for both the client and the contractor. The conclusion is that there is a need for clearer and more consistent guidelines that can promote a predictable and fair allocation of risk with regard to AB 04 chapter 6 section 10 item 1, as the current regulation is neither reasonable nor appropriate. This, in turn, can strengthen trust between the parties and hopefully reduce the risk of disputes related to this provision.
Keywords: AB 04; Avtalsrätt; Bästa tekniska och ekonomiska resultat; Civilrätt; Entreprenadavtal; Entreprenadrätt; Förmögenhetsrätt; Löpande räkning; Självkostnadsprincipen